KEAMANAN DATA DAN INFORMASI PADA ERA DIGITAL PADA REMAJA PONDOK PESANTREN DAAR EL HIKAM CIPUTAT - Saprudin; Dian Megasari; Deanna Durbin Hutagalung (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Abstract In realizing the Tri Dharma of Higher Education through the Research and Community Service Institute (LPPM) of Pamulang University, it is necessary to carry out research activities that are adapted to the resources of the teaching staff. In essence, this community service activity is carried out to bridge the problems faced by the community, the community in general to educational institutions. In a digital era like today, internet media has become integrated into people's lives, especially teenagers in the school environment, it does not rule out the possibility of dangers that can damage their future. Seeing these dangers, there is a need for socialization or introduction to crimes that may occur in the digital world or the internet. The methods used in this community service activity are lectures, discussions and training. Through this activity, the Daar El Hikam Islamic boarding school in Ciputat is getting to know young people what will happen if they are not careful when using the internet. In the training conducted by a team of Pamulang University lecturers, teenagers made personal account security both when using laptops, PCs and personal cellphones to prevent the emergence of data contained in the devices used. Some of them create 2-step levers, recognize malicious apps on the phone, protect accounts with strong passwords. In this case, it is hoped that the youth of the Daar El Hikam Islamic boarding school in Ciputat will be more introspective and protect themselves in using the internet.